Mechanism of Fatigue Induced by Different Cycling Paradigms With Equivalent Dosage - Hsu, Miao-Ju; Chan, Hsiao-Lung; Huang, Ying-Zu; Lin, Jau-Hong; Hsu, Heng-Hsiang; Chang, Ya-Ju (Frontiers in Physiology, 2020)
Leg cycling is one of the most comm.modes of exercise used in athletics and rehabilitation. This study used a novel cycling setting to elucidate the mechanisms, central vs peripheral fatigue induced by different resistance with equivalent works (watt*min). Twelve male adults received low and relatively high resistance cycling fatigue tests until exhausted (RPE>18) in two weeks. The maximal voluntary contraction, voluntary activation level, and twitch forces were measured immediately before and after cycling to calculate General (GFI), central (CFI), and peripheral (PFI) fatigue indices of knee extensors, respectively. The results showed that the CFI (high: 92.26%±8.67%, low: 78.32%±11.77%, p=.004) and PFI (high: 73.76±17.32%, low: 89.63±11.01%, p<0.017) were specific to the resistance of fatigue protocol. The GFI is influenced by the resistance of cycling to support the equivalent dosage. This study concluded that the mechanism of fatigue would be influenced by the resistance of fatigue protocol although the total works had been controlled.